On the Historiography of the Rise and Demise of the Third Worldism - Özgür Balkılıç (Akademik İncelemeler Dergisi)
After 1945, Western countries witnessed the awakening of the Third World. People of underdeveloped countries, who had been subjected to domination by developed Western countries, showed an interest towards a project of the Third World; the underlying motto of which was shaped by disarmament, peace, and social and economic justice. This project aimed to embody a radical break from the economic, political, social, and cultural paths which were devised in the West and then imposed on the rest of the world. This paper will analyze the historiography of this project. In this context, this paper will approach such literature from the lenses of social movements that emerged in the Third World, of nation states and of international relations. Through social movements, it will firstly focus on the people’s struggles in the different regions of the so-called Third World. Secondly, the paper will analyze academic works whose main subject is the anti-imperialist struggles of different nationalist governments. And lastly, it will criticize scholarly works on the Non-Alignment Movement, whichpursued an anti-imperialist and anti-colonialist political agenda at the international level.